Pelatihan Problem Solving Bagi Orang Tua Anak Usia Dini Generasi Alpha Di TK Raudhatul Jannah - Inayah Kencanawati; Fhakita Indira Haris; Hasmawaty Hasmawaty (KARYA: Journal of Educational Community Service, 2023)
The community service activity carried out was a PAUD Seminar with the topic Problem Solving in Early Childhood Care in the Digital Era. Consisting of 20 parents, 3 teachers, 1 principal, and 5 students who are carrying out Teaching Assistance activities at Raudhatul Jannah Kindergarten. This service program aims to make parents, teachers and school principals more familiar with problem solving for children and the efforts that can be made. The implementation methods used in this service are presentation, lecture and discussion methods. The results of this service activity were measured using a pre-test and post-test for participation to determine the increase in understanding before and after being given PAUD seminar material: Problem Solving in Early Childhood Care in the Digital Era. The collected data was then analyzed using the Wilcoxon Test with the help of SPSS, the results of which showed that the data Asymn (2-tailed) = 0.01 < 0.05, meaning that there was a significant difference between participants' understanding before and after being given the PAUD Seminar. The results of the service showed that there was an increase in participants' understanding of child care and also an increase in participants' understanding of problem solving that could be done in child care in the digital era.